Androgen deprivation therapy use with post‐prostatectomy radiotherapy in the Prostate Cancer Outcomes Registry Victoria. Issue 1 (8th October 2018) - Ong, Wee Loon; Foroudi, Farshad; Evans, Sue; Millar, Jeremy
Abstract: Introduction: The aim of this study is to evaluate the use of androgen deprivation therapy (ADT) with post‐prostatectomy radiotherapy (PPRT) in a population‐based cohort of Australian men. Methods: This is a prospective cohort of men with localised prostate cancer captured in the Prostate Cancer Outcomes Registry Victoria (PCOR‐Vic), who received PPRT between January 2010 and December 2015. The primary outcome was ADT use with PPRT. Multivariate logistic regressions were used to identify patient, tumour and institutional factors influencing ADT use. Results: 485 men were included in this study – 115 (24%) had pT2 disease, 231 (48%) pT3a, 134 (28%) pT3b and 5 (1%) pT4. Eighteen (4%) men had ISUP grade 1 disease, 139 (29%) ISUP grade 2, 170 (35%) ISUP grade 3 and 158 (33%) ISUP grade 4/5, while 267 (64%) men had positive surgical margins. Median time from prostatectomy to PPRT was 8.1 months (IQR = 5.3–13.9). Sixty‐six (14%) patients had ADT with PPRT. In multivariate analyses, men who had increased age (OR = 1.06; 95% CI = 1.01–1.11), seminal vesicle involvement (OR = 3.81; 95% CI = 1.63–8.91) and underwent treatment in regional centres (OR = 2.17; 95% CI = 1.08–4.33) were more likely to have ADT with PPRT. Conclusion: We reported that 14% of men treated with PPRT received ADT in a population‐based cohort of Australian men, which was less than half of the proportion of ADT use with PPRT in the US. It will be of interest to evaluate the uptake of ADT with PPRT in the coming years following recent publications of level 1 evidence confirming overall survival benefits of ADT with PPRT.